A Situational Leadership Framework for Enhancing the Survival and Sustainability of SMEs in Botswana's Agrifood Sector - Ndebele, Gugulethu; Okharedia, Akhabue A. (Archives of Business Research, 2025)
This research aims to develop a Situational Leadership style Framework for the survival and sustainability of Small and Medium Enterprises (SMEs) in Botswana's Agriculture and Food (Agrifood) Sector. Toward this end, this study adopts a convergent mixed-methods methods approach. The data is collected through physical questionnaires and in-depth interviews. A simple linear regression model is estimated using the R programming language for quantitative data analysis. The qualitative data is analysed using thematic analysis, verbatim transcription, and quotations. The research examines the Situational Leadership style and its influence on the survival and sustainability of SMEs in the Agrifood Sector in Botswana. The study's findings indicate that the Situational Leadership style significantly influences SMEs' survival and sustainability in Botswana's Agrifood Sector. The contribution to knowledge is the Situational Leadership framework for leadership styles that depicts the emerging leadership styles from this study: mentorship, coaching, flexible, responsive, agile, adaptable, empowering, and exemplary leadership. These emerging leadership styles are depicted in the Situational Leadership framework, which identifies leadership styles that influence the survival and sustainability of SMEs in Botswana's Agrifood Sector. The study's main limitation is that a Google Scholar search yielded no results from previous matching studies that researched how the Situational Leadership style influences the survival and sustainability of SMEs in the Agrifood Sector in Botswana. However, this limitation does not necessarily affect the study's validity because the research findings can be generalised to other SMEs, since SMEs tend to face similar survival and sustainability challenges.